2023
DOI: 10.3390/jcm12062103
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in Patients with Diabetic Peripheral Neuropathy-Related Complaints: A Randomized Controlled Clinical Trial

Abstract: Background: Diabetic polyneuropathy (DPN) is a common complication of diabetes, which presents with a loss of sensorimotor function or pain. This study assessed the effectiveness and safety of acupuncture as a treatment for DPN-related complaints. Methods: In this randomized controlled trial, patients with type II diabetes and symptoms of neuropathy in the lower limbs were included. A total of 12 acupuncture treatments were administered over 8 weeks. The waitlist control group received the same acupuncture tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The mean velocity (33.1 ± 18.7 m/s) and mean amplitude (3.7 ± 2.1 µV) at baseline were low; an indication of DPN’s presence (Table 1 ). More information about the study population can be found in the publication reporting the primary results of the study 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean velocity (33.1 ± 18.7 m/s) and mean amplitude (3.7 ± 2.1 µV) at baseline were low; an indication of DPN’s presence (Table 1 ). More information about the study population can be found in the publication reporting the primary results of the study 15 .…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcomes of the ACUDPN study regarding the effects of acupuncture were the DPN related complaints at week 8, measured on a 0–100 mm visual analogue scale, and have been published elsewhere 15 . Gender, age, BMI, and duration of neuropathy were collected at baseline together with other demographical and medical data.…”
Section: Methodsmentioning
confidence: 99%
“…If acupuncture is trialed, the semi-standardized acupuncture in diabetic peripheral neuropathy (ACUDPN) treatment protocol with bilateral acupuncture points is recommended. 119 …”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“…Moderate level evidence suggests favorable utilization of acupuncture as an optional treatment for PDN. [117][118][119][120] Numerous prospective clinical studies and RCTs suggest a positive effect with relatively low adverse event rates. 119,[121][122][123][124][125] A singleblinded, placebo-controlled RCT compared acupuncture to sham acupuncture demonstrated low-moderate treatment effect without appreciable side effects, meanwhile another RCT found that pain was improved at week 12 of follow-up but efficacy waned by week 18 when acupuncture was compared to standard of care.…”
Section: Section 4 Alternative Approachesmentioning
confidence: 99%
“…In DPN, it has demonstrated a beneficial effect reducing pain and neuropathic symptoms, that upgrade patient’s life quality; and may even induce an improvement in NCS [ 26 29 ]. However, it is not yet clearly described whether these interventions may modify other responses, such as molecular or genetic profiles in humans, since there are few randomized controlled trials (RCTs) [ 13 , 27 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%